DISEÑO DE UN SISTEMA DE MONITOREO REMOTO DEL DESPLAZAMIENTO DE LOS TUBOS DE EXTENSIÓN DE UNA JUNTA EXPANSIVA PARA TUBERÍA TRANSPORTADORA DE HIDROCARBUROS (2017)
In 2012, Electronic Engineering Program at the University of the Coast through the research group GIECUC, executed an innovation project for the development of a device, called expansion joint, to reduce breakage of pipes in the transport of hydrocarbons caused by landslides or linear expansion. Proposed solution involves the displacement of two tubes which extend the device, relieving tension and slowing the rupture of the pipe. The measurement of displacement needs to be monitored to determine how soon the rupture occur and take corrective actions to prevent spillage of hydrocarbons or accidents in the area. Then, a system of electronic monitoring with graphical user interface that facilitates the visualization of displacement remotely is proposed, complementing the expansion joint. Operators can maintain the monitored pipe and react in time. The tests performed showed the functionality of the proposed system in the expansion joint.